Strategi Pembelajaran Dalam Dialog Nabi Khidir As Dan Nabi Musa As Serta Relevansinya Dengan Pendidikan Islam Era Digital (Telaah Tafsir Tarbawi Qs. Al-Kahfi Ayat 60-82) - Ahmad Naufal Hafidh; Nilna Fadlillah; Ida lutfiyatul Jamilah (DAARUS TSAQOFAH Jurnal Pendidikan Pascasarjana Universitas Qomaruddin, 2024)
Effective learning strategies are an important aspect to equip students from the negative impacts of the digital era, while the fact is that there are still many teachers who have not implemented effective learning strategies and many teachers who have not been able to follow digital transformation in the world of education. The purpose of this study is to discuss the educational strategies contained in the dialogue between Prophet Musa and Prophet Khidir and the relevance of these learning strategies in the reality of Islamic education in the digital era. The type of research used is library research with a qualitative-destructive approach. Data sources in this study include primary data sources in the form of data that are directly related, namely the Al-Qur'an, books of interpretation, and other sources, as well as secondary data in the form of data that are indirectly related in the form of journals, books, and other sources. The analysis that will be used uses an inductive mindset, which starts with facts in the world of education, then discusses, (1) the values ​​of educational strategies by finding between educational theories and tarbawi interpretations of surah Al-Kahf Verses 60-82; and (2) the relevance of the educational strategy in Surah Al-Kahf Verses 60-82 with Islamic education in the digital era.